First records and two new species of sipunculans (Sipuncula) from the Southern Mexican Pacific - Silva-Morales, Itzahí; Gómez-Vásquez, Julio D. (European Journal of Taxonomy, 2021)
Sipunculans are a poorly studied group in the Tropical Eastern Pacific. For the Southern Mexican Pacific (SMP) there is only one record of a sipunculan species. The main objective of this work was to determine the species composition of the phylum Sipuncula present in the SMP. The study area covered three Mexican states: Guerrero, Oaxaca and Chiapas; specimens from 28 localities were examined from both intertidal and subtidal zones. A total of 551 specimens were reviewed, from which 11 species were identified. Five of them have previously been recorded in the Tropical Eastern Pacific (TEP): Apionsoma (A.) hespera comb. nov., A. (Edmondsius) pectinatum, Aspidosiphon (A.) elegans, Phascolosoma (P.) puntarenae and Themiste (T.) hennahi; four species are similar to nominal species: Sipunculus (S.) cf. polymyotus, Siphonosoma cf. vastum, Siphonosoma cf. cumanense and Phascolosoma (P.) cf. perlucens; and two new species are described: Aspidosiphon (Paraspidosiphon) cutleri sp. nov. and Aspidosiphon (Paraspidosiphon) pastori sp. nov. A checklist and an identification key for all sipunculan species from the TEP are presented. The checklist includes 53 taxa, 25 of which are questionable records. This work generated 11 new records of sipunculans in the SMP and five new records in the TEP.